Prediction of Vehicle Braking Deceleration Based on BP Neural Network. Issue 1 (1st January 2022) - Zhang, Shen; Li, Da; Du, Feng; Wang, Tao; Liu, Yunpeng
Abstract: Abstract:This paper first introduces the BP neural network, upgrades and optimizes the neural network according to the actual demand, and then establishes the prediction model of vehicle braking deceleration according to the relevant parameters affecting vehicle deceleration. According to the vehicle relative distance, vehicle relative speed, front vehicle acceleration, collision time and lateral distance, the vehicle deceleration is predicted and analyzed. After data verification, the vehicle braking deceleration prediction model is more accurate for vehicle deceleration prediction, and the established prediction model is effective.